Burden, predictors and temporal relationships of comorbidities in patients with hidradenitis suppurativa: a hospital‐based cohort study. (16th September 2019) - Jørgensen, A.‐H.R.; Yao, Y.; Ghazanfar, M.N.; Ring, H.C.; Thomsen, S.F.
Abstract: Aim: To examine the burden, predictors and temporal relationships of comorbidities in patients with hidradenitis suppurativa (HS). Methods: Information on HS and ten systemic comorbidities was obtained by interview and clinical examination, including blood pressure, body mass index (BMI) and blood samples, in a cohort of consecutive HS outpatients. Results: A total of 302 patients were included. About 86.6% had at least one comorbidity. The mean number of comorbidities per patient was 2.1. One or more cardiovascular comorbidities were observed in 76.5% with evidence of substantial unawareness and undertreatment; 48.4% had hypertension, 9.3% had diabetes, 57.7% had dyslipidaemia and 36.7% were obese. About 6.6% had inflammatory bowel disease, 6.3% had arthritis, 29.5% had a psychiatric diagnosis, 5.6% had psoriasis, 7.9% had obstructive lung disease, and 6.6% had polycystic ovary syndrome. These comorbidities occurred at different time points in relation to the onset of HS with evidence of shared as well as differential risk factors. Age (per year), HR = 0.87 (0.79–0.96), P  <   0.006, age of onset of HS (per year), HR = 1.26 (1.14–1.40), P  <   0.001, male sex, HR = 2.51 (0.88–7.16), P  =   0.086, Hurley stage III (vs. Hurley I + II), HR = 3.46 (1.25–9.58), P  =   0.017, BMI (per unit), HR = 1.12 (1.04–1.20), P  =   0.002, and blood glucose (per unit), HR = 1.27 (1.16–1.39), P  <   0.001 were significant predictors for onset of diabetes. Conclusion: There is a substantial burden, unawareness and undertreatment of several systemic comorbidities in patients with HS. Comorbidities occur at different time points in relation to the onset of HS. This should lead to higher awareness among treating specialists.